ANALISIS TINGKAT PLAGIARISME PADA PROPOSAL TESIS SISWA MENGGUNAKAN SOFTWARE TURNITIN - Marliza Oktapiani; Sutiono Sutiono; Mu’allimah Rodhiyana; Ziyah Sya’ban Fadilatus; Zahra Amalia Salim (Akademika : Jurnal Teknologi Pendidikan, 2023)
The field of education should serve as an example in all actions, prioritizing commendable attitudes so that students possess the ability and sense of responsibility for their work. In creating theses, students often use the same references, exhibit similarity in thesis titles, replicate research methods, and some even merely change the location and research subjects while maintaining the same topic. This study explores the level of plagiarism in 79 thesis proposals of students at the Faculty of Islamic Religion, As-Syafi'iyah Islamic University, through a recapitulation of Turnitin results. This research aims to determine the level of plagiarism in thesis proposals using Turnitin software. The research method employed is qualitative, involving the calculation of the percentage of plagiarism in students' thesis proposals. This research indicates that the plagiarism level in the introduction section of students' thesis proposals shows an average similarity index of 64%, categorized as moderate. In the theoretical study section, the average similarity index is 71%, categorized as high, while in the research methodology section, the average similarity index is 68%, categorized as moderate. In general, this information can be used as a basis for university leadership to implement tasks for students that encourage enriching references, fostering reading interests, and understanding how to paraphrase in every scholarly writing.